2013
DOI: 10.1038/eye.2013.153
|View full text |Cite
|
Sign up to set email alerts
|

What does the future hold for the treatment of Fuchs endothelial dystrophy; will ‘keratoplasty’ still be a valid procedure?

Abstract: Fuchs endothelial corneal dystrophy (FECD) is a well recognized corneal disorder characterized by the presence of collagenous warts extending from Descemet membrane (guttae) and endothelial cellular dysfunction due to cell loss and/or degeneration. Because of the characteristic abnormal cell morphology as seen with specular microscopy as well as the limited regenerative capacity in vivo, the endothelial cells were considered to be 'dystrophic'. Hence, FECD is commonly managed by replacement of the endothelium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 59 publications
0
17
0
1
Order By: Relevance
“…This impact of peripheral damage is most prominent in PACE where there is no recipient endothelium to contribute to maintenance of the endothelial population of the graft. However, cell loss is most likely moderated in Fuchs' dystrophy by contribution of the recipient endothelium not affected by the disease, 24 particularly if there is excellent posterior wound apposition between the recipient bed and the donor. The end result observed clinically is profound central endothelial cell loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This impact of peripheral damage is most prominent in PACE where there is no recipient endothelium to contribute to maintenance of the endothelial population of the graft. However, cell loss is most likely moderated in Fuchs' dystrophy by contribution of the recipient endothelium not affected by the disease, 24 particularly if there is excellent posterior wound apposition between the recipient bed and the donor. The end result observed clinically is profound central endothelial cell loss.…”
Section: Discussionmentioning
confidence: 99%
“…Given the limited ability for cell division in the donated endothelial population, stabilization in ECD in at least the grafts for Fuchs' dystrophy may be as a result of the contribution of recipient endothelium over the donor bed. 24 Limitations of the previously mentioned analyses on endothelial cell loss are that they do not account for correlated data from repeated measures on the same subject or the selective dropout among subjects with lower ECDs who are more likely to experience graft failure. The latter is particularly important to capture because a model for such cell loss could be biased by the selective loss of eyes with low ECDs.…”
Section: Discussionmentioning
confidence: 99%
“…The apparent reason for this difference in efficacy may lie in the fact that with bullous keratopathy there may be a significant depletion of host corneal endothelial cells, whereas in Fuchs endothelial dystrophy, the endothelium of the peripheral cornea may be relatively spared. This is especially as Fuchs endothelial dystrophy probably represents a phenotypic continuum with a significant genetic overlap, and in some situations there could be a mosaic of nonaffected and affected cells [18]. Therefore, it appears that both donor and remaining host endothelial cells play a role in the restoration of corneal clarity after DMET.…”
Section: Donor Versus Host Endothelium: What Drives the Recovery?mentioning
confidence: 98%
“…In addition to removing the contact inhibition, it is possible that by removing the dysfunctional Descemet membrane and guttae that the physical barriers to cell migration are removed and that the bare corneal stroma is a better substrate for cell migration. 18 Recently, in vitro studies have shown that, when endothelial cells are grown on a patterned scaffold to mimic guttae, the formation of a monolayer is much slower than cells grown on a smoother surface. 85 Similar findings were seen in vivo in 3 patients who underwent descemetorhexis.…”
Section: Cellular Proliferationmentioning
confidence: 99%